2022
DOI: 10.1186/s12933-022-01542-4
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 inhibitors for secondary prevention in patients with cardiovascular diseases: a bayesian network meta-analysis

Abstract: Background The Food and Drug Administration has approved Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) inhibitors for the treatment of dyslipidemia. However, evidence of the optimal PCSK9 agents targeting PCSK9 for secondary prevention in patients with high-risk of cardiovascular events is lacking. Therefore, this study was conducted to evaluate the benefit and safety of different types of PCSK9 inhibitors. Methods Several databases includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 48 publications
0
34
0
6
Order By: Relevance
“…It was reported that the use of alirocumab was associated with reductions in all-cause mortality compared with control, while evolocumab was associated with increased all-cause mortality compared with alirocumab. These results suggest that alirocumab might provide the optimal bene ts regarding all-cause mortality with relatively lower SAE risks, and evolocumab might provide the optimal bene ts regarding myocardial infarction for secondary prevention in patients with high-risk of cardiovascular events 40 . Further research con rmed that inclisiran also has a potent lipid-lowering effect 41 .…”
Section: Discussionmentioning
confidence: 80%
“…It was reported that the use of alirocumab was associated with reductions in all-cause mortality compared with control, while evolocumab was associated with increased all-cause mortality compared with alirocumab. These results suggest that alirocumab might provide the optimal bene ts regarding all-cause mortality with relatively lower SAE risks, and evolocumab might provide the optimal bene ts regarding myocardial infarction for secondary prevention in patients with high-risk of cardiovascular events 40 . Further research con rmed that inclisiran also has a potent lipid-lowering effect 41 .…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, prolonged lowering of LDL-cholesterol is associated with lower risk of atherosclerotic cardiovascular disease [ 25 ]. Accordingly, “the lower, the better” paradigm has introduced potent lipid lowering strategies in clinical field, including ezetimibe and proprotein convertase Subtilisin/Kexin 9 inhibitors in addition to statin therapy [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the results of the ORION-3 trial showed well-tolerated safety profile consistent with other trials during 4 years of follow-up [ 44 ]. The network meta-analysis of PCSK9 inhibitors revealed that inclisiran was identified as the top ranked drug in association with less serious adverse events by the surface under the cumulative ranking curve, and there were no findings that LDL-C lowering therapies with PCSK9 mAbs and inclisiran were associated with new-onset diabetes and neurocognitive disorders [ 55 ].…”
Section: Inclisiran: a Small Interfering Ribonucleic Acid-based Inhib...mentioning
confidence: 99%